Ob sedemdesetletnici dopisnega člana Slovenske akademije znanosti in umetnosti dr. Ludvika Karničarja - Orožen, Martina (Slavia Centralis, 2020)
Retired professor of Slovene studies in Graz and corresponding member of SAZU Ludvik Karničar celebrated his 70th birthday.
Keywords: 70th birthday; Ludvik Karničar; retired professor; Slovene studies in Graz; Slovene studies